2001
DOI: 10.1002/cne.1326
|View full text |Cite
|
Sign up to set email alerts
|

The inner ear macular sensory epithelia of the Daubenton's bat

Abstract: The inner ear macular sensory epithelia of the Daubenton's bat were examined quantitatively to estimate the area and total number of hair cells. Ultrastructural examination of the sensory epithelium reveals two main types of hair cells: the chalice-innervated hair cell and the bouton-innervated hair cell. The existence of an intermediate type, with a nerve ending covering the lateral side of the hair cell, indicates that the chalice-innervated hair cells are derived from bouton-innervated hair cells. Thus, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…A previous study on Daubenton's bat reported statistically significant differences between stereocilia numbers on striolar and extrastriolar hair cells (Kirkegaard and Jorgensen 2001); in contrast to the present results, striolar bundles in the bat had significantly fewer stereocilia than extrastriolar bundles. Two other studies have suggested that type I hair cells may have more stereocilia than type II hair cells based on indirect evidence: comparisons of a mixed population of bundle types with a population of known type II bundles (Peterson et al 1996) or extrapolations from partial stereocilia counts (Morita et al 1997).…”
Section: Accurate Identification Of Hair Cell Typecontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous study on Daubenton's bat reported statistically significant differences between stereocilia numbers on striolar and extrastriolar hair cells (Kirkegaard and Jorgensen 2001); in contrast to the present results, striolar bundles in the bat had significantly fewer stereocilia than extrastriolar bundles. Two other studies have suggested that type I hair cells may have more stereocilia than type II hair cells based on indirect evidence: comparisons of a mixed population of bundle types with a population of known type II bundles (Peterson et al 1996) or extrapolations from partial stereocilia counts (Morita et al 1997).…”
Section: Accurate Identification Of Hair Cell Typecontrasting
confidence: 99%
“…The reason for this is that bundle structure is known to vary with location in amniote vestibular organs (e.g., Jorgensen 1989; Kirkegaard and Jorgensen 2001;Lim 1976Lim , 1979Lindeman 1969;Peterson et al 1996), and without holding location constant, it is impossible to know whether observed differences between type I and type II bundles are due to effects of spatial locus or effects of hair cell type. In turtle utricle, type I hair cells have significantly more stereocilia than type II hair cells, even when location is held constant (i.e., when all measured bundles are within the striola or even within zone 3).…”
Section: Known Locationmentioning
confidence: 99%
“…We hypothesized that type I HCs might be replaced by type II HCs since type II-to-I HC conversion has been suggested to occur after ototoxin-induced HC loss in avian utricles (Weisleder and Rubel, 1993; Zakir and Dickman, 2006). Additional support for this hypothesis was provided by Kirkegaard and Jørgensen (2001), who detected individual HCs that appeared to be a hybrid with properties of both type I and type II HCs in vestibular organs of adult bats. However, when we fate-mapped type II HCs in mice under normal conditions, there was no evidence of type II-to-I conversion over an 8-month period of early adulthood (Figure 10B).…”
Section: Discussionmentioning
confidence: 84%
“…In mice, vestibular HC production is reported to occur only during gestation and the first two postnatal weeks (Ruben, 1967; Rüsch et al, 1998; Kirkegaard and Nyengaard, 2005; Burns et al, 2012). However, dying and immature-appearing HCs have been detected in utricles under normal conditions in adult guinea pigs (Forge et al, 1993; Li et al, 1995; Rubel et al, 1995; Lambert et al, 1997; Forge et al, 1998; Forge and Li, 2000) and bats (Kirkegaard and Jørgensen, 2000, 2001). The ability of adult rodents to regenerate small numbers of utricular HCs after ototoxin-induced damage is another indicator of plasticity in mammalian vestibular epithelia (Forge et al, 1993; Warchol et al, 1993; Forge et al, 1998; Kawamoto et al, 2009; Golub et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1956;Engström et al, 1974;Nordemar, 1983;Sá nchez-Ferná ndez and Rivera-Pomar, 1983;Favre et al, 1986;Park et al, 1987;Mbiene et al, 1988;Lysakowski, 1996;Lysakowski and Goldberg, 1997;Ross, 1997;Rü sch et al, 1998;Kirkegaard and Jørgensen, 2001). Synaptogenesis in the vestibular SE has also been studied in other species, including cats Sans, 1977, 1979;Favre et al, 1986), chickens (Ginzberg and Gilula, 1980), and humans (Sá nchez-Ferná ndez and Rivera-Pomar, 1983; Sans and Dechesne, 1987).…”
Section: Production Of New Hair Cells In Mature Mammalian Vestibular Sementioning
confidence: 95%